2020
DOI: 10.1155/2020/4975628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Short-Term Efficacy and Safety of Guselkumab for Moderate-to-Severe Plaque Psoriasis: Meta-Analysis of Randomized Controlled Trials

Abstract: Background. To investigate the efficacy and safety of guselkumab in the treatment of moderate-to-severe plaque psoriasis. Methods. A systematic review was undertaken to identify double-blind randomized controlled trials (RCTs). PubMed, Web of Science, Cochrane Library, EMBASE, and Google Scholar databases were searched before 1 March 2020. The odds ratios (ORs) with 95% confidence interval (CI) were calculated. All analyses were conducted with intention-to-treat basis. A range of sensitivity analyses was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…To the Editor: Guselkumab and risankizumab, human monoclonal antibodies targeting interleukin (IL)-23, have been recently approved for the treatment of moderate-to-severe plaque psoriasis. 1 Even if clinical trials reported consistent efficacy and safety data, 2,3 real-life studies are scant with no existing comparison survey. Hence, we performed a retrospective cohort real-life study to compare indirectly their efficacy and safety.…”
Section: Guselkumab and Risankizumab For Psoriasis: A 44-week Indirect Real-life Comparisonmentioning
confidence: 99%
See 3 more Smart Citations
“…To the Editor: Guselkumab and risankizumab, human monoclonal antibodies targeting interleukin (IL)-23, have been recently approved for the treatment of moderate-to-severe plaque psoriasis. 1 Even if clinical trials reported consistent efficacy and safety data, 2,3 real-life studies are scant with no existing comparison survey. Hence, we performed a retrospective cohort real-life study to compare indirectly their efficacy and safety.…”
Section: Guselkumab and Risankizumab For Psoriasis: A 44-week Indirect Real-life Comparisonmentioning
confidence: 99%
“…Phase III trials have shown guselkumab and risankizumab as very effective drugs, reporting superiority to antietumor necrosis factor, antieIL-12/23 and antieIL-17, high percentage of complete skin clearance (47.4%-56.3% at week 48-52) together with an optimal safety profile. 2,3 These results need to be confirmed in real-life settings, dealing with more complicated patients (eg, multiple comorbidities, polypharmacy, common previous biologic failure), which usually do not meet trials' inclusion criteria. 1 Interestingly, our real-life survey did not highlight any particular difference among guselkumab and risankizumab in terms of mean PASI, BSA, PASI 90, PASI 100, and AE frequency up to 44 weeks.…”
Section: Guselkumab and Risankizumab For Psoriasis: A 44-week Indirect Real-life Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Since there is an ongoing phase 2 clinical trial to evaluate whether dupilumab is effective for moderate to severe chronic hand eczema refractory to potent topical corticosteroids ( NCT03861455 ) 27 , it remains to be seen. Guselkumab was initially approved for moderate-to-severe psoriasis and palmoplantar pustulosis 28 29 . Because pustules occasionally appear in hand eczema, particularly impetiginized or vesiculopustular type, palmar pustulosis is an important and challenging differential diagnosis of chronic hand eczema; however, guselkumab is not indicated for chronic hand eczema.…”
Section: Resultsmentioning
confidence: 99%